Adaptive Reuse of Historic Heritage Buildings: A Case Study of Unye - ATMACA, Göksu; REYHAN, Kader (Journal of Interior Design and Academy, 2021)
Historical buildings are tangible assets that reflect our past as a cultural heritage. It is of great importance to conserve and transfer these immovable cultural assets to future generations. The sustainability of these values, which act as a bridge between the past and the future, is directly proportional to their use. After being restored, every structure left to itself will face the situation of disappearance and destruction again. In this context, adaptive reuse, which is preferred as one of the conservation methods, is the bringing to life of cultural values that complete their existence functionally but continue their existence physically, partially or completely, with another function after the restoration phase. In this article, the contribution of the changes in the interior design to the cultural sustainability as a result of the new function in historical buildings is examined. The aim of this study is to examine the historic heritage buildings that have gained a new function with the Cultural Road Project, within the scope of adaptive reuse, which is one of the conservation methods for transferring historical buildings to future generations. In the content of the study, the historical development and architectural features of the selected examples are examined, and then the restoration evaluation based on these features and all dimensions of adaptive reuse that completes this evaluation are discussed. In the formation of the study, literature review was initially made, subsequently, visual data and oral information about historical buildings were collected from the relevant people through field survey. Collected data, then then examined and evaluated in the frame of concept.